Role of Interpersonal Communication Channels in the Uptake of Cervical Cancer Screening among Women in Uasin Gishu County, Kenya - Judy B, Chepngeno; Anyonje Lydia; Anyonje Lydia (International Journal of Applied Sciences: Current and Future Research Trends, 2023)
Cervical cancer remains a serious health challenge in the developing world due to various reasons. Among these reasons are low uptake of screening services owing to poor access to reliable information about cervical cancer, role of screening and treatment options. This paper examines the role of interpersonal communication channels in the uptake of cervical cancers screening services among women in Uasin Gishu County. The study was guided by Diffusion of Innovations (DOI) theory. It utilized mixed methods research design. The target population of the study was all women within the reproductive age of 18-65 years seeking maternal child health services and family planning (MCH-FP) at Moi Teaching and Referral Hospital in Uasin Gishu County, Kenya. The study used systematic random sampling method to obtain a sample of 308 from the population. Purposive sampling was used for the key informants, namely 4 health workers and 2 County officers from the Ministry of Health. Two focus group discussions (FGDs) were conducted among women with each group composed of 10 women. Data from the FGDs and key informant interviews were used to generate qualitative data. For quantitative data, the study utilized questionnaires for data collection. Quantitative data was analysed using descriptive statistics with the aid of SPSS, version 29. Qualitative data was analysed thematically. The study found that women rely on several channels of communication to access and disseminate cervical cancer information. The most common channels of communication used are friends, health care workers and media channels. From the study findings, it is also concluded that interpersonal communication channels play a key role in the uptake of cervical cancer screening. As such, it is recommended that the major stakeholders, namely the national and county governments, together with non-governmental organizations working in the health sector in Kenya, should make deliberate efforts to formulate policies to guide effective dissemination of cervical cancer messages for prevention, early detection and treatment of cervical cancer.